1993
DOI: 10.1089/aid.1993.9.307
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Triciribine and Triciribine-5′ -Monophosphate Against Human Immunodeficiency Virus Types 1 and 2

Abstract: Triciribine (TCN) and its 5'-monophosphate (TCN-P) are novel tricyclic compounds with known antitumor activity; TCN-P is currently in phase II human clinical trials. We now report that these compounds have potent and selective activity against HIV-1 and HIV-2. Using a syncytial plaque assay, TCN and TCN-P were active against HIV-1 at 0.01-0.02 microM and had differential selectivities of 2250 and 1900, respectively, compared to 1850 for AZT. In contrast, TCN and TCN-P had minimal selectivity against human cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…In 1971, Schram and Townsend synthesized triciribine 30 , a tricyclic derivative of a purine nucleoside as a potential anticancer drug, which has also been studied as an antiretroviral agent against HIV-1 and HIV-2 . Triciribine 30 , however, is poorly soluble, and this suboptimal property led to the development of the highly soluble prodrug triciribine-5′-monophosphate 33 .…”
Section: Enzyme Inhibitor and Cell Surface Receptor Antagonist Nucleo...mentioning
confidence: 99%
“…In 1971, Schram and Townsend synthesized triciribine 30 , a tricyclic derivative of a purine nucleoside as a potential anticancer drug, which has also been studied as an antiretroviral agent against HIV-1 and HIV-2 . Triciribine 30 , however, is poorly soluble, and this suboptimal property led to the development of the highly soluble prodrug triciribine-5′-monophosphate 33 .…”
Section: Enzyme Inhibitor and Cell Surface Receptor Antagonist Nucleo...mentioning
confidence: 99%
“…33 These studies also found no cross resistance to TCN or TCN-P in AZT-or TIBO-resistant HIV strains.33 Similar to its antiproliferative activity in L1210 cells, TCN must be phosphorylated to TCN-P to be active against HIV. 34 Together with the data on the lack of cross resistance, the results suggest that TCN and TCN-P have an entirely different mode of action than AZT or TIBO.…”
Section: Introductionmentioning
confidence: 81%
“…Furthermore, cytotoxicity such as that observed in murine L1210 cells appears to be highly cell line specific3 and was not observed in human cell lines used to propagate HIV and human cytomegalovirus (HCMV). 33 Studies on the antiviral mechanism of action of TCN are currently underway.…”
Section: Introductionmentioning
confidence: 99%
“…TCBN is a tricyclic adenosine analog that is phosphorylated to its active metabolite (TCBN‐P) by adenosine kinase in certain cells, such as the lung epithelial cells (Wotring et al, 1986). TCBN can inhibit viral replication of HIV‐1 and HIV‐2 independent of Akt, including strains known to be resistant to azidothymidine or TIBO (Kucera et al, 1993). The phosphorylation of TCBN to TCBN‐P has been reported to be essential for its antiviral activity on HIV‐1 (Porcari et al, 2003; Ptak et al, 2010).…”
Section: Discussionmentioning
confidence: 99%